Face Feature Change Detection Ability in Developmental Prosopagnosia and Super-Recognisers - Jodie Davies-Thompson (Brain Sciences, 2024)
In non-clinical populations, facial features (eyes, nose, mouth) may vary in their contribution to face identity perception. Changes to whole faces are easier to detect than changes to individual features, and eye changes being able to detect than mouth changes which in turn are easier to detect than nose changes. However, how this differs for people with face recognition difficulties (developmental prosopagnosia; DP) and for individuals with superior face recognition abilities (super-recognisers; SR) is not clear; although findings from previous studies have suggested differences, the nature of this difference is not understood. The aim of this study was to examine whether differences in the ability to detect feature changes in DPs and SRs were a) quantitative meaning that the pattern across feature changes remained the same but there was an overall upwards or downwards shift in performance, or b) qualitative meaning that the pattern across feature changes were different. Using a change detection task in which individual face features (eyes, nose, mouth) changed between sequentially presented faces, we found that while prosopagnosics showed a quantitative difference in performance with a downwards shift across all conditions, super-recognisers only showed qualitative differences - they were better able to detect when the face was the same and were marginally, close to significantly worse at detecting when the eyes changed. Further, the only condition which distinguished between the three groups, was the ability to identifying when the same face was presented, with SRs being better than controls, and controls being better than DPs. Our findings suggest that, in feature matching tasks, differences for DPs are due to them being overall worse at the task, while SRs use a qualitatively different strategy.